Thermal Analysis of Radial Piezoelectric-Magnetic Fan (RPMF) for Electronics Cooling - Abdul Razak, Fadhilah; Ahmad, Robiah; Sarip, Shamsul (International Journal of Integrated Engineering, 2018)
Application of piezoelectric fan in electronic cooling system has been proven that it is more efficient than natural convection with least power consumption and has high potential to replace existing rotary fan for its simplicity and longer life. An integration of piezoelectric fan with magnet is to widen the cooling coverage area with similar power consumption and cost of running a single piezoelectric fan. By optimizing the repulsive magnetic force generated in between the magnets, the overall fans oscillate with significant average amplitude. The purpose of this paper is to investigate the performance of multiple piezoelectric-magnetic fan and its significance in reducing temperature while enhance the heat transfer. The parameters under investigation are the distance between magnets and fans orientation. In this study four magnetic fans were activated by a piezoelectric fan. Â It is found that at distance between magnets is 14 millimeters; the average amplitude is largest at highest resonant frequency. The multiple fans is better to be arranged in radial orientation for its ability to produce larger repulsive magnetic force to oscillate the adjacent fans. The distribution of repulsive magnetic force in radial orientation is five times better than array orientation. Therefore, radial piezoelectric-magnetic fan (RPMF) produces larger average amplitude of fans which is 111%. 30% of power consumption per unit coverage area is secured. RPMF generates average wind velocity of 0.4m/s compared to array orientation 0.17m/s.